2024
DOI: 10.1085/jgp.202313464
|View full text |Cite
|
Sign up to set email alerts
|

Transport of metformin metabolites by guanidinium exporters of the small multidrug resistance family

Rachael M. Lucero,
Kemal Demirer,
Trevor Justin Yeh
et al.

Abstract: Proteins from the small multidrug resistance (SMR) family are frequently associated with horizontally transferred multidrug resistance gene arrays found in bacteria from wastewater and the human-adjacent biosphere. Recent studies suggest that a subset of SMR transporters might participate in the metabolism of the common pharmaceutical metformin by bacterial consortia. Here, we show that both genomic and plasmid-associated transporters of the SMRGdx functional subtype export byproducts of microbial metformin me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…The research provides a comprehensive analysis of the SMRGdx subtype, including biochemical, structural, and mechanistic attributes. These findings are relevant not only to other members of the SMR family but also to other multidrug transporters (MDTs), proteins best known for their role in microbial antibiotic resistance (this issue: Lucero et al, 2024 ).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The research provides a comprehensive analysis of the SMRGdx subtype, including biochemical, structural, and mechanistic attributes. These findings are relevant not only to other members of the SMR family but also to other multidrug transporters (MDTs), proteins best known for their role in microbial antibiotic resistance (this issue: Lucero et al, 2024 ).…”
Section: Introductionmentioning
confidence: 94%
“… Lucero et al (2024) solved a crystal structure of Gdx-Clo in the presence of guanylurea to investigate if it occupies the same binding site as guanidinium in Gdx-Clo. The crystal structure of Gdx-Clo with guanylurea was solved up to 2.1 Å, which showed that guanylurea occupies the same binding pocket as Gdm + in Gdx-Clo.…”
Section: The Smr Family and Metformin Transportmentioning
confidence: 99%
See 1 more Smart Citation